Challenges and progress in the development of a serogroup B meningococcal vaccine. - Lewis, S; Sadarangani, M; Hoe, J; Pollard, A (2009)
Serogroup B meningococci cause the majority of the meningococcal disease burden in developed countries. Production of an effective and safe vaccine for serogroup B organisms has been hampered by the poor immunogenicity of the capsular polysaccharide that defines this group of bacteria. Previous efforts have focused on outer membrane vesicle vaccines, which have been implemented successfully during clonal outbreaks. However, the search for a universal vaccine against endemic polyclonal serogroup B meningococcal disease continues. In this review, we have highlighted recent development of outer membrane vesicle vaccines and progress in the evaluation of recombinant outer membrane protein vaccines.